History of Science and Technology - Gutnyk, Maryna; Tverytnykova, Olena; Radohuz, Serhii (National technical university "Kharkov politechnical institute", 2024)
In the modern world, filled with profound changes and global interdependence, humanitarian knowledge has gained fundamental importance. Humanities disciplines play a crucial role in shaping not only professional competencies but also a deep understanding of the essence of modern challenges. The study of humanitarian aspects, including the course “History of Science and Technology,” becomes an integral element of the educational process. This course not only repeats what is already known from school programs but conducts in-depth and systematic analysis of historical and cultural aspects. An important feature is that it reveals the history and science of Ukraine in the context of their interaction with world civilization. This course provides students with the opportunity to develop not only technical skills but also contributes to the disclosure of their deeper understanding and analysis of various aspects of the modern world. The study of the history of science and technology helps create a harmonious personality that carries a significant correlation between technical capabilities and humanitarian understanding. At the same time, this course helps overcome narrow technocratic thinking, expanding the horizons of students and making them more comprehensively prepared for the challenges of the present. The study of the history of science and technology contributes to the creation of intellectually mature individuals with a higher sense of conscious responsibility and dignity. They are capable of seeing more than just technical aspects and understand how their actions affect the global community. The course “History of Science and Technology” illustrates how technological development is related to social context, cultural values, and historical circumstances. This helps create graduates who not only possess technical knowledge but also understand their consequences for humanity as a whole. The study of the history of science and technology is a necessary element in forming a deep and comprehensive approach to education, promoting the creation of future leaders capable of making informed and morally justified decisions in the modern globalized world. The exam tasks are composed of individual variants and contain questions of various levels of complexity, allowing for the most objective assessment of the students' level of preparation. The recommended preparation time is 1 week. The student needs to review the lecture notes provided by the teacher and master the necessary knowledge assigned for independent study. The literature necessary for this is presented at the end of the guidelines.
Історія науки та техніки: методичні рекомендації для підготовки до заліку для усіх спеціальностей
Keywords: history of science and technology; chemistry; physics; biology; scientific revolution; scientist